Urgensi Desain Pembelajaran Berbasis Soft Skill di Perguruan Tinggi - Makruf, Syahdara Anisa (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
Â Learning based on soft skill and hard skill is essential in college. The problem that often arises is that there are still many lecturers who design their learning based on hard skills only. This is because some lecturers do not understand the importance of learning based on soft skill. This research uses library research approach to examine how iurgency of learning design based on soft skill in college. The result shows that the design of learning based on soft skill in college aims to realize the students who believe in God and become an independent and responsible person. Thus, learning based on soft skill is relevance because it is a capital for students to be able to manage themselves and respect in social life. The lecturers could teach soft skill values in three ways, namely: lecturer role model, message of the week, and hidden curriculum.Â Ø¥Ù Ø§ÙØªØ¯Ø±ÙØ³ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ÙØ§ÙÙÙØ§Ø±Ø§Øª Ø§ÙØµØ¹Ø¨Ø© Ø£ÙØ± Ø£Ø³Ø§Ø³Ù ÙÙ Ø§ÙÙØ³ØªÙÙ Ø§ÙØ¬Ø§ÙØ¹Ù. ÙØ§ÙÙØ´ÙÙØ© ÙÙ ÙØ§ÙØ²Ø§Ù ÙØ«ÙØ± ÙÙ Ø§ÙÙØ¯Ø±Ø³ÙÙ ØµÙÙÙÙØ§ ØªØ¯Ø±ÙØ³ÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙØµØ¹Ø¨Ø©Â  ÙÙØ·. ÙØ°Ø§ ÙØ£Ù Ø¨Ø¹Ø¶Ø§ ÙÙÙÙ ÙÙ ÙÙÙÙÙØ§ Ø¬ÙÙØ¯Ø§ ÙØ¹ÙÙ " Ø§ÙØªØ¹ÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ". ØØ§ÙÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« â Ø¨ÙØ¯Ø®Ù Ø§ÙØ¨ØØ« Ø§ÙÙÙØªØ¨Ù â Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙØ¹ÙÙÙØ© ÙÙÙ ØªØµÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ÙØ£ÙÙÙÙØªÙ ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø§Øª. Ø¯ÙÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£Ù ØªØµÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø§Øª ÙÙ Ø¨ÙØ¯Ù Ø¥ÙØ¬Ø§Ø¯ Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØ¤ÙÙÙÙ Ø¨Ø§ÙÙÙØ ÙØ§ÙÙØªÙÙÙ Ø§ÙÙÙØ ÙØ§ÙÙØªØ®ÙÙÙÙ ÙÙÙÙÙÙØ§ Ø£Ø´Ø®Ø§ØµØ§ ÙØ¹ØªÙØ¯ÙÙ Ø¹ÙÙ Ø£ÙÙØ³ÙÙ ÙØ°ÙÙ Ø§ÙÙØ³Ø¤ÙÙÙØ©. Ø¨ÙØ°Ø§ ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ÙÙØ§Ø³Ø¨ ÙÙÙÙÙ ÙÙÙÙÙ Ø¹Ø¯ÙØ© ÙÙØ·ÙØ§Ø¨ ÙÙÙÙÙÙØ§ ÙØ§Ø¯Ø±ÙÙ Ø¹ÙÙ Ø¥Ø¯Ø§Ø±Ø© Ø£ÙÙØ³ÙÙ ÙÙÙÙ ÙØ¹Ù ÙÙ Ø§ÙØÙØ§Ø© ÙØ¹ ÙØ¬ØªÙØ¹ÙÙ. ÙÙÙÙÙ ÙÙÙ ÙÙÙ Ø§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ÙÙ Ø§ÙÙØØ§Ø¶Ø± Ø¥ÙÙ Ø§ÙØ·ÙØ§Ø¨ Ø¹Ù Ø·Ø±Ù Ø«ÙØ§Ø« ÙÙÙ : 1) ÙØ«Ø§ÙÙØ© Ø§ÙÙØØ§Ø¶Ø±Ø 2) Ø§ÙØ±Ø³Ø§Ø¦Ù Ø§ÙØ£Ø³Ø¨ÙØ¹ÙØ©Ø 3) Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù Ø§ÙØ®ÙÙÙ. Â